Reboot the world - Abd Razak, Dzulkifli (2010)
IN the next few days, Malaysia is poised for another turning point. This will mark another milestone for Malaysia's future in its journey towards Wawasan 2020 a vision carved out some 20 years ago to realise an advanced nation status. We have completed more than twothirds of the sojourn and have faced major challenges along the way. But we have also chalked up many achievements that have given us the strength to see us through the next decade!